Unraveling School Adolescent Depression: Insights into Cognitive Behavioral Therapy - Gang, Liu; Jais, Samsiah Mohd (Universitas Negeri Medan, 2024)
Adolescent depression presents a significant global mental health concern, exerting profound impacts on various facets of young people's lives. Cognitive Behavioral Therapy (CBT) has emerged as a leading intervention for tackling adolescent depression, grounded in principles derived from cognitive theory. This review delves into the effectiveness, mechanisms, and outcomes of CBT in addressing adolescent depression, synthesizing findings from a range of empirical studies including randomized controlled trials, meta-analyses, and systematic reviews. The review underscores the consistent efficacy of CBT in diminishing depressive symptoms among adolescents, elucidating mechanisms such as cognitive restructuring and behavioral activation that underpin its therapeutic effects. Additionally, CBT yields favorable outcomes beyond mere symptom reduction, encompassing enhancements in social connections and academic performance. Nonetheless, challenges such as limited accessibility and hurdles in engaging adolescents persist in CBT implementation. To surmount these obstacles, forthcoming research ought to concentrate on devising innovative delivery approaches, such as internet-based interventions and school-centered programs. In essence, CBT stands as a pivotal component in the treatment of adolescent depression, furnishing a holistic framework to address the intricate interplay of cognitive, emotional, and behavioral elements, thereby fostering the mental well-being of adolescents on a global scale.